Reimaging internationalization in higher education in the post-COVID era - Heidtke, Sina (Journal of International Students, 2026)
This study explores the internationalization of student mobility at higher education institutions (HEIs), specifically in the post-COVID era. The opportunities and challenges in the internationalization of student mobility for non-degree-seeking students are examined through a systematic literature review (SLR) using the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) framework. During and after the pandemic, HEIs worldwide have faced major challenges in reimplementing internationalization within student mobility. The objective of this study is to employ the matrix system of Webster and Watson (2002) to categorize the identified literature. Facilitating the identification of essential columns that are considered indispensable in the post-COVID era. The findings of these studies provide a foundation for further research approaches and offer recommendations and implications to support HEIs in developing strategies to increase the number of international students at the international level.